Hyperhydricity-Induced Physiological Changes and Catechin Accumulation in Blueberry Hybrids (Vaccinium corymbosum × V. angustifolium) - Rajesh Barua; Sayani Kundu; Abir U. Igamberdiev; Samir C. Debnath (Horticulturae)
Hyperhydricity is a significant challenge in the tissue culture of blueberry plantlets, affecting their propagation, survival and quality, which results in economic losses for industrial blueberry micropropagation. The in vitro liquid propagation of two half-highbush blueberry hybrids, HB1 and HB2, showed that a Growtek stationary bioreactor culture system containing a liquid medium exhibited a higher hyperhydricity percentage than a Sigma glass culture system with a semi-solid medium. The percentage of hyperhydricity (75.21 ± 1.89%) and water content (72%) of HB2 was more than that of HB1. A scanning electron microscopy study revealed that hyperhydric plantlets from both genotypes developed slowly, had closed stomata, and displayed enlarged intercellular spaces between the palisade and spongy parenchyma layers. Disrupted vascular bundles, underdeveloped sieve elements and a weak connection between phloem and xylem tissue were also observed in hyperhydric plantlets. An analysis of mesophyll and stem tissues highlighted a compressed adaxial epidermis, which led to compact palisade parenchyma, with irregularly shaped mesophyll cells. Hyperhydric plants showed strong nuclear magnetic resonance (NMR) signals in the aliphatic, aromatic, and sugar regions, specifically at peaks of 2.0, 2.5, 4.0, 4.5, 6.0, and 6.7 ppm. These signals were attributed to the presence of catechin (C15H14O6), a flavonoid compound, suggesting its significant role or accumulation in these plants under hyperhydric conditions. Despite the negative effects of hyperhydricity on commercial propagation, hyperhydric plants were found to contain higher levels of valuable untargeted metabolites, such as β-P-arbutin, chlorogenic acid, quercetin-3-O-glucoside, epicatechin, 2-O-caffeoyl arbutin, various fatty acids, β-glucose, linolenic acid, and acetyl than both in vitro and ex vitro conditions. The enrichment of bioactive compounds in blueberry enhances its antioxidant properties, nutritional profile, and potential health benefits, making them significant for plant defense mechanisms and stress adaptation.